The Notion of Americanism - Nasiba, Sattarova (International Journal on Integrated Education, 2023)
The focus of researchers studying the active processes that are associated with the influence of American English on other languages and their variants is the concept of "Americanism". It should be admitted that the term Americanism, like the corresponding English americanism, has a broad meaning and is used in different senses, not only linguistically.